Routes to market in the toys and games industry - Brennan, Ross, 1957-; Canning, Louise; McDowell, Raymond (London : SAGE Publications Ltd, 2017)
Berchet is a French supplier of traditional toys; it sells primarily into the French and the UK markets, and manufactures most of its products in Hungary and China. Toy producers who deal with retailers on a regular basis are subject to periodic reviews of their serviceability. The review would typically feature as part of the supplierretailer meetings and consists of: Profit Performance, Delivery Performance, and Quality of Contact.
Originally published in Brennan, R., Canning, L., & McDowell, R. (2014). Routes to Market in the Toys and Games Industry. Business-to-business marketing (3rd ed., pp. 317320). London: SAGE Publications Ltd. Print. ISBN: 9781446273722.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Berchet; Toy industry -- France; Toy industry -- Great Britain; Toys -- France -- Marketing; Toys -- Great Britain -- Marketing